Influence of pulverized palm kernel and egg shell additives on the hardness, coefficient of friction and microstructure of grey cast iron material for advance applications - Enesi Y. Salawu; Oluseyi O. Ajayi; Anthony Inegbenebor; Stephen Akinlabi; Esther Akinlabi (Results in Engineering, 2019)
Previous studies showed the effects of organic carbon on the mechanical properties of alloys. However, the mechanisms of graphite films formation have not been given due attention. In the present study, diffusion of carbon content via heat treatment process to produce graphite films is presented using microstructure. Consequently, the graphite films formed a protective layer on the heat treated metals which cause hardness increase and in turn improved the wear resistance of the heat treated material due to reduced coefficient of friction. The excellent tribological properties of carburized grey cast iron showed the potentials of palm kernel and egg shell for advance material modifications. Keywords: Hardness, Cast iron, COF, Microstructure